Korean Taboo Expressions Among Indonesian K-Pop Netizens - Agus Darma Yoga Pratama (RETORIKA: Jurnal Ilmu Bahasa, 2026)
This study examines how Indonesian K-pop fans use pseudo-Korean language in online conflicts that cross national borders. The clash between Seablings and Knetz has become a major online event. Through qualitative netnography, the research examines how Indonesian 'Seablings' and Korean netizens interact on X (Twitter), focusing on hybrid words like kontolyo and knetzteu. The results show that pseudo-Korean is a flexible system with creative suffixes and unique endings. Fans use this playful language to turn taboo words into inside jokes, which helps them build community and solidarity. More broadly, these language forms are used to challenge power dynamics between cultural centres and digital outsiders. By looking at these practices, the research shows how language innovation can shape identity, community, and resistance in the digital age.